Radial movements and lower limb joint kinematics during the takeoff phase of kicking pullovers - Konosu, A.; Yoshioka, S.; Yanagihara, D.; Fukashiro, S. (International Journal of Sport & Health Science, 2020)
The purpose of this study was to clarify the mechanisms and techniques of one-leg swing type takeoffs for acquiring vertical and angular momentums of backward rotation. The kinematics were measured for successful kicking pullovers performed by 12 adult males. Using a 12-segment rigid body link model, the contributions of each body parts to the vertical and angular momentums, the kinematics of both leg joints, and the accelerations of the body parts relative to hip joint of the support leg during the takeoff phase were calculated. The swing leg accelerated away from the ground during the takeoff phase, and was responsible for 64% of the vertical momentum and 43% of the angular momentum of the whole body at takeoff. The hip joint of the support leg extended to the limit of the range of motion at takeoff, achieving both an increase in ground contact time and a backward rotation of the trunk. We concluded that the swing leg greatly contributes to the acquirement of vertical and angular momentum of the whole body in one-leg swing type takeoffs including backward rotation. Specifically, swinging the swing leg using a large range of motion and fully extending the hip joint of the support leg hip joint are the two important technical elements to pre-tense the support leg muscles and increase the ground reaction impulse.